Case report: Systemic muscle involvement as the primary clinical manifestation of chronic active Epstein–Barr virus infection: A case-based review - Shi, Shanfen; Li, Liangda; Pan, Cuiping; Yang, Yandi; Chen, Gun; He, Yongping (Frontiers in Immunology, 2022)
Chronic active Epstein–Barr virus infection (CAEBV) is common in Asian countries and characterized by recurrent or persistent infectious mononucleosis-like symptoms. Here, we describe a rare case of CAEBV-associated generalized myositis with extranodal NK/T-cell lymphoma, who initially presented with swelling and muscle soreness in the extremities, and diagnosed as polymyositis at the initial stage. CAEBV-associated generalized myositis is different from polymyositis and other types of myositis. Furthermore, it is prone to lymphoma with poor prognosis.